The evaluation of evidence‐informed changes to an internationally educated nurse registration process. (27th May 2019) - Kwan, J.A.; Wang, M.; Cummings, G.G.; Lemermeyer, G.; Nordstrom, P.; Blumer, L.; Horne, N.; Giblin, C.
Abstract : Aim: To evaluate effectiveness of specific policy and practice changes to the process of registration for internationally educated nurses. Background: Little research exists to inform registration policy for internationally educated health professionals. Introduction: Internationally educated nurse employment can help address nursing shortages. Regulators assess competencies for equivalency to Canadian‐educated nurses, but differences in health systems, education and practice create challenges. Methods: The study setting was a Canadian province. We used a mixed methods approach, with a pre–post‐quasi‐experimental design and a qualitative evaluation. Previous analysis of relationships between applicant variables, registration outcomes and timelines informed changes to our registration process. Implementation of these changes composes the intervention. Comparisons between pre‐ and post‐implementation exemplar subgroups and timeline analyses were conducted using descriptive statistics, univariate analysis and non‐parametric tests. Data were collected from complete application files before ( n = 426) and after ( n = 287) implementation of the intervention. Interviews, focus groups and consultations were completed with various stakeholders. Findings: The time between steps in the process was significantly reduced following implementation. Stakeholders reported an increase in perceived efficiency, transparency and use of evidence. Discussion: Results indicated that initial impacts of the policy changes streamlined the process for applicants and staff. Conclusion: Maintaining a consistent and systematic review of an organization's data coupled with implementation of findings to effect policy and practice change may have an important impact on regulatory policy. Implications for Nursing Policy: These findings represent the beginning of an international policy conversation. Policy changes based on organizational data can underlie major process improvement initiatives. Ongoing nursing shortages across the globe and increasing mobility of nurses make it important to have efficient and transparent regulatory policy informed by evidence.